Cyclization Reactions Involving 2-Aminoarenetellurols and Derivatives of α,β-Unsaturated Carboxylic Acids - Jayna A. Patel; Aundrea M. Lee; Donna V. Franklin; Frank R. Fronczek; Thomas Junk (Heteroatom Chemistry)
The reductive cyclization of arenetellurols carrying α,β-unsaturated amide functionalities in the ortho position was investigated. Conceptually, such compounds can form 1,3-tellurazoles without the involvement of the unsaturation in the ring closure, they can form 1,4-tellurazinone derivatives, or they can undergo ring closure to 1,5-tellurazepinones. Amides derived from acrylic and methacrylic acid generated 1,5-tellurazepinones while 2-cinnamylamidobenzenetellurol cyclized to a 1,3-tellurazole derivative. In contrast, the reaction of acetylenedicarboxylic acid and its derivatives with 2-aminoarenetellurols generated 1,4-tellurazepinones, including a derivative of novel tricyclic naphtho [1, 4]tellurazinone. A comparison with analogous reactions of sulfur congeners indicates that their chemistry is a good predictor for the products obtained from 2-aminoarenetellurols. Selected compounds were characterized by X-ray crystallography. The present work offers access to previously unexplored organotellurium heterocycles.